PENGARUH KUALITAS PRODUK DAN DESAIN TERHADAP KEPUTUSAN PEMBELIAN DI DUTA PHONECELL KOTA BENGKULU - Ramadan, M. Alhasbi P. (UM. Bengkulu, 2025)
Consumer purchasing decisions are an integration process that combines knowledge to evaluate two or more alternative behaviors, and choose one of them. The purpose of this study is to find out the influence of product quality and design on purchase decisions at Duta Phonecell Bengkulu City. This type of research is a descriptive quantitative approach. The sample in this study is 50 consumers. The data collection techniques in this study are observation and questionnaire. The data analysis techniques used were multiple linear regression, determination coefficients, and hypothesis tests. It was obtained that there was an influence of product quality (X1) on the purchase decision (Y) of Duta Phoncell, where the value of sig < 0.05 (0.000<0.05) and the value of tcalcul>ttable (3.980> 1.666196) thus Ho was rejected and Ha was accepted. From the significance value obtained, the variable X1 has a positive effect on the purchase decision (Y). There is an influence of design (X2) on the purchase decision (Y) of Duta Phoncell where the value of sig < 0.05 (0.016<0.05) and the value of tcalcul>ttable (3,500>1.666196) thus Ho is rejected and Ha is accepted. From the significance value obtained, the variable X2 has an effect on the purchase decision (Y). The significance F value is < 0.05, which is 0.000 < 0.05 and Fcalcul>Ftable (17.060>3.10) so that it can be concluded that together independent variables have an effect on dependent variables. Keywords: Product Quality, Design, Purchase Decision